Optimizing Banjar Community Fiqh: Bahilah Practice for the Deceased in South Kalimantan - Jarajap, Inawati Mohammad Jainie; Anshari, Mukhlis; Naimah, Naimah; Hafidzi, Anwar; Lutfi, Lutfi (Potret Pemikiran, 2024)
This study examines the optimization of societal fiqh understanding within the Banjar community, focusing on the bahilah practice related to the payment of fidyah for missed prayers and fasting by the deceased in the Pahuluan community, South Kalimantan. The purpose of this research is to analyze how bahilah—a local tradition for fulfilling religious obligations for the deceased—is conducted and to understand its legal implications within the framework of Islamic law. The research employs a qualitative approach, utilizing observation, in-depth interviews, and document analysis. Data was collected from the Pahuluan community to gather primary insights into the practice of bahilah and the challenges faced by heirs in fulfilling fidyah obligations. The findings indicate that the practice of bahilah often involves the use of the concept of hilah (legal stratagem) to ease the burden on the heirs. However, this practice also raises issues, such as the validity of fidyah payments when the recipients do not meet the criteria of being impoverished, and the execution of grants that do not always comply with the essential requirements of Islamic law. The implications of this study highlight the need for increased community understanding of the proper implementation of bahilah in accordance with Islamic legal principles, as well as the necessity for oversight and guidance from religious scholars or authorities to ensure that this tradition aligns with the applicable Sharia regulations.